The Role of Literature and Art in Social Movements in Contemporary Elementary Schools - Simanjuntak, Nensy Megawati; Sumartono, Sumartono; Wardhani, Widya Desary Setia; Sugianto, Iwan; Sari, Fransiska Marta (Mimbar Sekolah Dasar, 2025)
The lack of literary and artistic resilience has contributed to heightened stress and social conflict in elementary school learning. This issue highlights the urgency of re-examining the role of literature and art in educational practices, particularly in supporting social movements within elementary schools to address increasingly complex social dynamics. The main objective of this study is to analyze the contribution of literature and art in strengthening students’ social and emotional resilience within the elementary school curriculum. The research employed a quantitative approach with a sample of 450 participants, consisting of 400 students and 50 teachers from elementary schools in Surabaya, selected using stratified random sampling. Data were collected using a validated questionnaire with a five-point Likert scale and analyzed through descriptive statistics and linear regression with the assistance of SPSS Version 29.0. The results revealed that literature and art significantly improved students’ perceptions and participation in developing social and emotional resilience, with mean scores of 62.5% and 59.5% respectively. These findings confirm the effectiveness of arts-based and literature-oriented education in fostering social-emotional competencies. In conclusion, literature and art play complementary roles in shaping students’ resilience in contemporary educational contexts. The practical implications suggest that integrating literature and art more systematically into the curriculum can enhance social awareness, promote solidarity in learning, and foster tolerance among students. Furthermore, such integration provides a sustainable framework for cultivating both individual resilience and collective harmony in school environments.